qHBsAg for the Identification of Liver Histological Abnormalities in HBeAg-Negative Chronic Hepatitis B Patients with Normal and Mildly Elevated ALT Levels - Qinyi Gan; Yan Huang; Chuanwu Zhu; Shuang Zhao; Haoshuang Fu; Minghao Cai; Jiexiao Wang; Chenxi Zhang; Simin Guo; Zhujun Cao; Qing Xie (Canadian Journal of Gastroenterology and Hepatology)
Backgrounds. Noninvasive detection of histological abnormalities remains challenging in patients with HBeAg-negative chronic HBV infection with normal or mildly elevated levels of alanine aminotransferase (ALT). This study aimed to assess the utility of serum quantitative hepatitis B surface antigen (qHBsAg) in identifying significant histological lesions in this population. Methods. This is a single-center study with retrospective analysis of 392 treatment-naive patients of HBeAg-negative chronic HBV infection with normal or mildly elevated levels of ALT. Results. In this cohort, significant necroinflammation and fibrosis were found in 69.4% and 61.5% of patients, respectively. Patients with qHBsAg >1000 IU/mL (N = 236) had more hepatic inflammation of ≥G2 (75.4% vs. 60.9%, P<0.01) or fibrosis ≥ S2 (66.1% vs. 54.5%, P<0.05) compared to those without (N = 156). Serum HBsAg (cutoff point = 1000 IU/mL), aspartate aminotransferase (AST) level (cutoff point = 25 IU/L), age (cutoff point = 40 years), and HBV family history were identified as independent predictors of significant histological abnormalities in multivariate logistic analysis. Conclusions. A significantly higher proportion of patients with histological abnormalities were found in patients with qHBsAg >1000 IU/mL than those without. The qHBsAg level together with age, AST, and family history of HBV infection could be used as an algorithm to help noninvasive patient selection for antiviral therapy.